Transformasi Kesadaran Pedagogik Mahasiswa PGSD melalui Evaluasi Diri Berbasis Video dan Flipped Classroom dalam Praktik Microteaching: Transformation of Pedagogical Awareness of Elementary School Teacher Education Students through Video-Based Self-Evaluation and Flipped Classroom in Microteaching Practice - Canni Loren Sianturi; Sepriandison Saragih (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2025)
Microteaching practice is a strategic space in pre-service teacher education to develop comprehensive pedagogical competencies. However, various studies show that pre-service teacher students often display awkward, mechanical, and self-centred teaching performance in the early stages of practice. This study aims to examine in depth how video-based self-evaluation combined with the Flipped Classroom approach can transform the pedagogical awareness of PGSD students in microteaching practice. This study used an explanatory sequential mixed methods design with a case study approach in one class of fifth-semester PGSD students (N = 16) at HKBP Nommensen University, Pematangsiantar. Quantitative data were obtained through microteaching assessment scores before and after the video-based self-evaluation, which were assessed by the lecturer and analysed using a paired sample t-test. Qualitative data were collected through students' written reflections and analysis of video recordings of teaching practice. The results showed a significant increase in the quality of students' microteaching performance (Mean = 9.81; t(hit) = 6.96; p < 0.05) after implementing the video-based self-evaluation within the Flipped Classroom framework. This improvement is reflected in material mastery, questioning skills, classroom management, utilization of learning media, and a shift in learning orientation from teacher-centred to student-centred. Qualitatively, student reflections revealed a transformation in pedagogical awareness characterized by increased teaching readiness, sensitivity to student learning needs, and the ability to design more contextual, participatory, and meaningful learning. These findings confirm that video-based self-evaluation within the Flipped Classroom framework serves not only as a technical reflection tool but also as a medium for shaping the professional identity of prospective teachers.